THE IMPACT OF ANXIETY ON THE SUCCESS OF EXCLUSIVE ASI, CHILDREN'S GROWTH AND DEVELOPMENT - Uly Artha Silalahi; Endang Astiriyani; Bayu Irianti (Jurnal Smart Kebidanan, 2024)
Pregnant women experience many psychological changes that can result in prenatal stress. This condition can cause further anxiety and tension, thus forming a feedback cycle that can increase overall emotional intensity. The aim of this research is to analyze the influence of anxiety during pregnancy on the success of exclusive breastfeeding, child growth and development . The population in this study were all children aged 20-24 months with a total of 100 children in the Taman Sari District, Tasikmalaya City . The research results showed that 50 people (50%) had maternal anxiety during pregnancy. The results of the Chi square analysis test on maternal anxiety during pregnancy on the success of exclusive breastfeeding obtained a P value of 0.016. Maternal anxiety during pregnancy on child growth P value 0.008. On maternal anxiety during pregnancy towards child development P value 0.022 . So it can be concluded that there is an influence of maternal anxiety during pregnancy on exclusive breastfeeding, child growth and child development